PENDIDIKAN ISLAM DI MESIR - Zainal Hakim (EDUCATIONAL JOURNAL : General and Specific Research, 2021)
The education curriculum developed in Egypt uses national education standards based on the needs of educational development in Egypt. This national standard applies to all levels and types of education. The Educational Leveling System Developed is Elementary School (Ibtida'i), Junior High School (I'dadi), High School (Tsanawiyah 'Ammah), Higher Education.